SZ - Kultur : Zitate + Ausschnitte + Salzgitterkulturnachrichten. - Baier, Alexander; Büttenbender, Ilona; Michels, Inge; Zörner, Hendrik; Museum Schloss Salder und Kulturamt, Salzgitter (Salzgitter, : Stadt Salzgitter, 1990)
Gelpke, André ; Baier, Andreas ; Hajek, Katja ; Rosen, Hartmut ; Kubach ; Kortekaas, Huub ; Kerm, Stephan ; Röhm, Vera ; Hajek, Otto Herbert ; Schoenholz, Michel ; Hashimoto ; Lechner, Alf
Duits
kunstcatalogus